Capgras and Fregoli delusions - a case report - M. Viseu; F. Tavares; M. Barbosa Pinto (European Psychiatry, 2022)
Introduction Capgras and Fregoli delusions are psychotic complex conditions that integrate a larger group of Delusional Misidentification Syndromes (DMS), where the patient misidentifies people, places or objects.